Building customer loyalty in selected food establishment at SM Manila: a consumer preference study - Aggabao, Mary Ann Jamaica C. Austin,Rosannie J. Cunanan, Ma. Angelica U. Eud,Marc Adrian R. MiguelJohn Levin D. and Salcedo.Raul Jr. A. 4 0 16; 5
NO ABSTRACT.
Undergraduate Thesis: (B.S. Hotel and Hospitality Management) - Pamantasan ng Lungsod ng Maynila 2016.
Keywords: 2 -- 0; 6; 20; 20; 2